2018
DOI: 10.1053/j.gastro.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Reduces DNA Integrity in Sperm From Men With Inflammatory Bowel Disease

Abstract: There are few data on the effects of methotrexate on reproductive capacity in men with inflammatory bowel diseases (IBDs). We performed a case-control study to determine the effects of methotrexate on sperm quality and genetic integrity. We compared sperm samples from 7 men with IBD who had been exposed to methotrexate for at least 3 months with sperm samples collected from 1912 age-matched men at fertility centers (controls) where sperm parameters would be expected to be worse than those of the general popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Six studies reporting fertility outcomes in patients exposed to methotrexate (MTX) were identified. These studies included a total of 47 cases (40 men diagnosed with psoriasis and seven with IMD) and 1912 controls (all controls come from one study ( Ley et al , 2018 )). In patients exposed to MTX, sperm concentration decreased in three studies ( Van Scott and Reinertson, 1959 ; Sussman and Leonard, 1980 ; Pandhi et al , 2006 ), no differences were reported in two studies (one study reported five normal testicular biopsies after MTX exposure) ( El-Beheiry et al , 1979 ; Ley et al , 2018 ) and the sperm quality of one group of patients diagnosed with psoriasis and exposed to MTX was better than patients treated with high dose glucocorticoids ( Grunnet et al , 1977 ).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies reporting fertility outcomes in patients exposed to methotrexate (MTX) were identified. These studies included a total of 47 cases (40 men diagnosed with psoriasis and seven with IMD) and 1912 controls (all controls come from one study ( Ley et al , 2018 )). In patients exposed to MTX, sperm concentration decreased in three studies ( Van Scott and Reinertson, 1959 ; Sussman and Leonard, 1980 ; Pandhi et al , 2006 ), no differences were reported in two studies (one study reported five normal testicular biopsies after MTX exposure) ( El-Beheiry et al , 1979 ; Ley et al , 2018 ) and the sperm quality of one group of patients diagnosed with psoriasis and exposed to MTX was better than patients treated with high dose glucocorticoids ( Grunnet et al , 1977 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AZA/6‐MP did not appear to negatively affect sperm DNA integrity evaluated by using sperm chromatin structure assay (SCSA) and COMET assays 59 . IBD patients treated with MTX were reported in one study, in which patients were concurrently treated with IFN inhibitors or 5‐ASA 61 . Despite normal semen parameters, a higher percentage of sperm DNA fragmentation as well as oxidative stress adducts were reported, suggesting that MTX could impair male fertility by affecting sperm redox balance.…”
Section: Resultsmentioning
confidence: 99%
“…El-Beheiry et al [68] reported no significant abnormalities in terms of semen quality, testicular histopathological features, and spermatogenic activity in 26 men with psoriasis receiving MTX. Recently, Ley et al [69] published a case-control study that investigated the effects of MTX on sperm quality and genetic integrity. Notably, 7 men with IBD who received MTX for >3 months showed significantly decreased sperm integrity and DNA fragmentation and damage secondary to oxidative stress compared with age-matched men in a study performed across different fertility centers.…”
Section: ② ② Methotrexatementioning
confidence: 99%